Evaluation of the average pulp cavity volume of primary second molar and canine for obturation of a single primary tooth: A preliminary cone-beam computed tomographic study - Ritesh Kalaskar; Sudhindra Baliga; Shruti Balasubramanian (Wolters Kluwer Medknow Publications, 2021)
Objective: Metapex/Vitapex is one of the most commonly used obturating materials in pediatric dental practice in recent times. It is available in a premixed syringe which poses numerous practical difficulties. This study aimed to calculate the root canal volume of maxillary and mandibular canine and second molar using cone-beam computed tomography (CBCT) to determine the quantity/grams of obturation material to obturate a single tooth (mass = density × volume). Materials and Method: This nonrandomized clinical trial is comprised of two parts. The first part involved calculation of average root canal volume using CBCT which was used to calculate the quantity/grams of obturating material. This predetermined quantity was used to obturate primary mandibular second molars and canines, and the quality of obturation was assessed. Results: Assessment of quality of obturation showed optimum length obturation in 53.33% primary second molars and 66.66% primary canines. Conclusion: It can be inferred that even with the use of exact predetermined quantity/grams of obturating material, optimum quality obturation could be achieved, thus avoiding wastage, preventing cross contamination, and simultaneously offering good clinical results. Hence, this study opens further gateways to device ampules containing predetermined mass of obturating material for a single use for obturation of a single primary tooth.